A Mechanism for Reviewing Investments in Health Research Capacity Strengthening in Low- and Middle-Income Countries. Issue 1 (3rd August 2020) - Kilmarx, Peter H.; Maitin, Thabi; Adam, Taghreed; Akuffo, Hannah; Aslanyan, Garry; Cheetham, Michael; Corrêa-Oliveira, Rodrigo; Kay, Simon; Khelef, Nadia; Kunaratnam, Yaso; Kupfer, Linda; Olesen, Ole F.
More than 40 agencies that fund health research capacity strengthening in low- and middle-income countries (LMICs) participate in the ESSENCE Health Research initiative, which has established a mechanism for reviewing and coordinating their funding. Taken together, the expected outcomes of implementation of the review mechanism are increases in the efficiency and equity in health research capacity strengthening activities with decreased duplication of efforts. The overall goal is increased support of research on national health priorities as well as improved pandemic preparedness in LMICs, and, eventually, fewer countries with very limited research capacity.